STUDI LITERATUR UPAYA MENINGKATKAN LITERASI INFORMASI SISWA PADA MATA PELAJARAN BIOLOGI SELAMA BELAJAR DARING EFEK COVID-19 - Abdul Rasyid Fakhrun Gani; Ummi Zaimah; Siti Retno Wulandari (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aims to find out more about the efforts to improve students' information literacy in online learning of the covid-19 effect of biology. The type of research used in this paper is a literature review study. This research was carried out by analyzing research related to how to increase information literacy in online learning the effects of Covid-19 describing, evaluating and clarifying the research and then drawing conclusions. The result of this research is that information literacy is a very important skill for students. At this time of online learning, students who have good information literacy skills will have no difficulty in learning. However, there are problems with students that it is difficult to study at home. Even though the average high school student is able to use existing technology. Therefore, efforts are needed to improve student information literacy. The conclusion in this study, based on the results of the author's analysis, there are three ways to improve students' information literacy, the methods are 1) doing biology online learning effectively to increase student interest in learning and foster student curiosity, 2) the teacher provides many learning resources. as reading material in learning and increasing student insight, and 3) parents and teachers must work together in monitoring, facilitating, and motivating students to develop their learning patterns, so that learning takes place effectively and can improve student’s information literacy.